MOST film applied to windows and the effect on space heating - Hultén, Liam (My University, 2022)
A study was performed in Matlab simulink to observe the effect a molecular solar energy storage (MOST) film placed on windows have on the space heating and cooling of a room given the weather data from 2019 in gothenburg, sweden. As well as the half-life of the photoisomer’s effect on the efficiency. The study concluded that the MOST film was not an effective application in the Gothenburg climate. Though it showed that the lower half-times of the MOST molecules actually had a positive impact on the efficiency.